2021
DOI: 10.1039/d1tc02726c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin PTAA interlayer in conjunction with azulene derivatives for the fabrication of inverted perovskite solar cells

Abstract: Perovskite solar cells (PSCs) have reshaped the thin-film photovoltaic technology owning to their exceptional high power conversion efficiency (PCE) in conjunction with their low-cost and facile production. PSCs are fabricated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The biAz‐4TPA/PTAA bilayer leads to favorable energy‐level alignment that enhances the holes extraction process. [ 146 ]…”
Section: Engineering At Ptaa/perovskite Interfacementioning
confidence: 99%
“…The biAz‐4TPA/PTAA bilayer leads to favorable energy‐level alignment that enhances the holes extraction process. [ 146 ]…”
Section: Engineering At Ptaa/perovskite Interfacementioning
confidence: 99%
“…In recent years, it was found that the ultrathin PTAA polymers can be used to modify the surface of a roughed ITO thin film as the anode electrode, which can result in the high PCE of 18.11% [ 147 ]. The PCE of the ultrathin-PTAA-based inverted perovskite solar cells can be increased to be higher than 21% when the surface of the hydrophobic PTAA polymers is modified by using the bipolar organic molecules, such as PEAI and 3-(1-pyridinio)-i-propanesulfonate (PPS) [ 148 , 149 ].…”
Section: Understanding Of Highly-efficient Inverted Perovskite Solar ...mentioning
confidence: 99%
“…13 On the other hand, its highly hydrophobic properties will reduce the repeatability of the perovskite devices and cause pinholes after depositing the perovskite layer. 14,15 Self-assembled molecules (SAMs) have recently been used in p-i-n PSCs as HSLs, because of the advantages of cost-effectiveness, stability, and absence of additives. 16−18 Additionally, SAMs provide large-scale deposition capability due to their capacity to use different types of deposition techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A Poly­[bis­(4-phenyl)­(2,4,6-trimethylphenyl)­amine (PTAA) layer is widely used as an HSL in p-i-n configuration PSCs, and its highly hydrophobic properties lead to increased perovskite grain sizes and directly affect the performance of the perovskite devices . On the other hand, its highly hydrophobic properties will reduce the repeatability of the perovskite devices and cause pinholes after depositing the perovskite layer. , Self-assembled molecules (SAMs) have recently been used in p-i-n PSCs as HSLs, because of the advantages of cost-effectiveness, stability, and absence of additives. Additionally, SAMs provide large-scale deposition capability due to their capacity to use different types of deposition techniques. SAMs typically consist of the following three groups: an anchoring group that connects the small molecules to the metal oxide surface via chemical bonding, a spacer that controls the packing geometry, and a terminal group that adjusts the surface and interface properties. The control of interface properties has drawn attention due to improvement of the charge extraction with better energy alignment and reduced trap density. , Moreover, the terminal group determines the wettability of the SAMs which affects the grain size and consequently the grain boundaries of the perovskite layer .…”
Section: Introductionmentioning
confidence: 99%